El Paso del Norte - Modernisierungsdiskurse, Grenzziehungen und Management-Praxis in der Maquiladora-Industrie - Berndt, Christian (ERDKUNDE, 2001)
Starting from the assumption that Maquiladora managers play a crucial role in the current struggle for the discursive construction of the 'modern' Mexico, the author critically engages with these powerful actors and their representations of Maquiladora workers and the production environment. He seeks to show that in order to make the Maquiladora a production unit which 'works', foreign capital representatives create a discursive interface, that is, they construct collective identities and homogenize the actors making up the Maquiladora. One is faced by a complex, continuously changing social landscape which is made coherent by a discourse depicting the Maquiladora as a rationalizing force, a vehicle finally bringing Mexico on its way into the 'First World'. Justifying management practices which do not always square with frequent claims of learning and skilling, cultural stereotypes and inscriptions play an important role in stabilizing the subject positions of these powerful actors. However, a closer look at the various seemingly stable drawers into which Mexican 'others' are put reveals that the representations offered are in fact ambivalent and contradictory. These disjunctures provide openings for resistance on the part of weaker actors. Mexican workers, as well as members of the middle management, take the various inscriptions and re-appropriate them with different meanings. In doing so, borders are redrawn and rearticulated in a dialogical way. Yet the actors negotiating the social landscape of the Maquiladora industry are embedded in different social spheres which have different reach and provide unequal access to power resources. This makes it extremely difficult for less powerful groups to force through alternative interpretations of the Maquiladora, Ciudad Juárez and the US-Mexican border.